Construction of complexiton-type solutions using bilinear form of Hirota-type - Kaplan, Melike; Raza, Nauman (Walter de Gruyter GmbH, 2022)
Abstract In this paper, based on the Hirota bilinear form and the extended transformed rational function method, complexiton solutions have been found of the Hirota–Satsuma–Ito (HSI) equation and generalized Calogero–Bogoyavlenskii–Schiff equation through a direct symbolic computation with Maple. This method is the improved form of the transformed rational function method. The obtained complexiton solutions, includes trigonometric and hyperbolic trigonometric solutions, have verified utilizing Hirota bilinear forms. Also, a graphical representation of the obtained solutions is given.
Keywords: KdV equations (Korteweg-de Vries equations); Transform methods (e.g., integral transforms) applied to PDEs; complexiton solutions; extended transformed rational function method; symbolic computation